Platelet counting with the BD AccuriTM C6 flow cytometer. (May 2014) - Masters, Andrew; Harrison, Paul
Abstract The Accuri™ C6 is a compact flow cytometer that uses a peristaltic pump with a laminar flow fluidic system and can measure absolute cell counts. In this study we have evaluated this method with the International Reference Method (IRM) simultaneously measured on both the Accuri™ C6 and a reference flow cytometer. After optimisation of sample labelling conditions, final dilutions and flow cytometer settings, a comparison of the absolute fluorescent platelet count with the RBC/platelet ratio on the C6 and the IRM was then performed in 144 patient samples with a full range of platelet counts (range 2–650 × 109/l). The platelet/RBC ratio method determined on the Accuri™ agreed well with the IRM (R2 = 0.99, bias = 2.3 (Bland Altman) and R2 = 0.96, bias = 1.02 at counts <50 × 109/l). The absolute platelet count also agreed well with the IRM (R2 = 0.97, bias = −0.16 and R2 = 0.91, bias = 3.7 at <50 × 109/l). The C6 absolute platelet count and RBC/platelet ratio methods also agreed well (R2 = 0.99, bias = −2.5 and R2 = 0.95, bias = 2.71 at counts <50 × 109/l). Reproducibility studies on the C6 gave CVs of <5% for the RB/platelet ratio and <12% for the absolute cell counts. The C6 also demonstrated excellent linearity on diluted samples with both volume and ratio methods (R2 = 0.99). As one might expect, the absolute platelet count is therefore slightly more inaccurate than the RBC/platelet ratio particularly at platelet counts <50 × 109/l as it is likely to be more sensitive to pipetting error. The Accuri™ C6 provides a simple, rapid and reliable method for measuring platelet counts by either the RBC/platelet or direct volume methods. The direct volume method can also be used to determine platelet counts within purified platelet preparations or concentrates in the absence of RBC.